5G magnetic resonance coupling planar spiral coil wireless power transfer - Kamarudin, Saidatul Izyanie; Ismail, Alyani; Sali, Aduwati; Ahmad, Mohd Yazed; Ismail, Ismayadi; Navaie, Keivan (Walailak University, 2022)
Wireless Power Transfer in the 5G frequency band is the most promising technology to power up ubiquitous small electronic devices as well as IoT devices. A strongly coupled magnetic resonanceWPT technique that focuses on near-field electromagnetic energy has been proposed in this paper. However, most Magnetic Resonance Coupling Wireless Power Transfer (MRC WPT) applications have been designed in kHz and MHz frequency spectrum. This paper demonstrates Planar Spiral Coil Magnetic Resonance Coupling (PSC MRC) WPT designs at 5G (GHz) frequencies. Also, the transformation technique of the low frequency (kHz and MHz) magnetic resonance circuit model equations to high frequency (GHz) circuit model equations to achieve ahigh-efficiency power transfer. PSC MRC WPT designs structure antennas are designed at 3.4-3.5 GHz in the form of circular and square shapes with 1turn coil.The proposed antenna structures are firstly being optimized in a full-wave electromagnetic simulator, CST Microwave Studio to resonate at the 3.4-3.5 GHz band. Then, the close-loop equations to determine the efficiency of 5G Magnetic Resonance Coupling Planar Spiral Coil Wireless Power Transfer is designed. Lastly, the results are compared with the simulationand calculated parts. The highest efficiency of the PSC MRC circular antenna is 31.58 when the distance is at 2 mm, and 31.26 and 31.02 when the distance is at 3 and 4 mm, respectively.The efficiency of circular PSC MRC is found to be25better than the efficiency of square shape design.